Extraction of microwave FET noise wave temperatures by using a novel neural approach. Issue 1 (4th January 2016) - Ðorđević, Vladica; Marinković, Zlatica; Marković, Vera; Pronić-Rančić, Olivera
Abstract : Purpose: – The purpose of this paper is the development of an efficient approach for extraction of the microwave FET noise wave temperatures. Design/methodology/approach: – The proposed approach is based on an artificial neural network (ANN) trained to determine the noise wave temperatures from the given measured transistor noise parameters. Findings: – The presented approach enables not only efficient, but also an accurate direct extraction of the noise wave temperatures. This is confirmed by the validation of the proposed approach that is done by comparison of the transistor noise parameters obtained using the extracted noise wave temperatures with the measured noise parameters. Originality/value: – Application of ANN is a novel approach to extract the noise wave temperatures, which provides more efficient microwave FET noise wave modeling.